1983
DOI: 10.1002/cyto.990040110
|View full text |Cite
|
Sign up to set email alerts
|

A practical graphical method for estimating the fraction of cells in S in DNA histograms from clinical tumor samples containing aneuploid cell populations

Abstract: A graphical method for the analysis of unperturbed DNA histograms is presented in which the area of the normalized histogram subtended by the fraction of cells in S is represented by a trapezoid whose dimensions are dependent on features common to all such histograms. The technique takes measurement variability into account. This method was applied to a variety of synthetic DNA histograms. Overall, calculated values for the fraction of cells in S correlated well with actual values. This method was applied to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…S fractions were calculated from the DNA histograms by the method of Ritch et al (21), and aneuploidy peaks were identified and characterized using previously described criteria (24). Specifically, the identification of nontetraploid aneuploidy required the presence of a peak that was at least partially separated from the G, or G,M peak, and contained at least 5% of the cells in the population.…”
Section: Dna Histogram Analysesmentioning
confidence: 99%
“…S fractions were calculated from the DNA histograms by the method of Ritch et al (21), and aneuploidy peaks were identified and characterized using previously described criteria (24). Specifically, the identification of nontetraploid aneuploidy required the presence of a peak that was at least partially separated from the G, or G,M peak, and contained at least 5% of the cells in the population.…”
Section: Dna Histogram Analysesmentioning
confidence: 99%
“…From these graphs, individual debris contamination was determined as constants of a "background function" subtracted from the original frequency distribution in order to obtain a "cleaned" distribution ( were determined independently by the computerized Dean and Jett model (2) as well as graphically from the cumulative frequency curves (integral curves) of the "cleaned" DNA distributions, based on the trapezoidal model (19). Cell clumping artifacts such as doublets and triplets were eliminated mathematically using a modification of the formula given by Beck (1).…”
Section: Dna Flow Cytometry (Fcm)mentioning
confidence: 99%
“…For control of the validity of the graphical SPF values, two independent methods were used the Dean and Jett model (2) and a graphic method (19).…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the fraction of cells in S phase. The fraction of cells in S was determined by the method of Ritch et al (53). In diploidaneuploid mixtures that could be resolved either graphically or by dual parameter analysis, S fractions were calculated separately for each subpopulation.…”
Section: Clinical Samplesmentioning
confidence: 99%